Research on the water intake and drainage methods of the coastal nuclear power plants in China and the associated impacts on the Marine ecological environment(我国滨海核电厂取排水方式现状及其对海洋生态环境的影响) - 王薇(WANG Wei); 何桂萍(HE Guiping); 关骁倢(GUAN Xiaojie); 陈兆林(CHEN Zhaolin); 李德鹏(LI Depeng); 孙丽艳(SUN Liyan); 张冲(ZHANG Chong) (Zhejiang Daxue xuebao. Lixue ban)
With the rapid development of nuclear power in China, the ecological environmental protection attracted more attention. At present, all the nuclear power plants in China once-through cooling, and the construction of intake and drainage structures may affect the hydrodynamic and erosion environment. An alternative intake and drainage approach is by culvert. It shows that the influences on the hydrodynamic and erosion environment by culvert are less than vertical structures. The increase of flow velocity due to culvert structures is 0.01 m·s-1 within the area of north-south ±200 m and east-west ±100 m in the tidal direction, and the scour depth is greater than 0.3 m within the circular area centered at drainage outlet with radius of 200 m. The average flow velocity change introduced by vertical structures is 0.05 m·s-1 with the impact distance about 2.4 km, and the sedimentation thickness on both sides of the open intake channel is 0.2~1.0 m. In addition, the marine ecological environment include water intake, warm water and residual chlorine discharge on the aquatic organisms. It is suggested that the optimization of drainage scheme should be comprehensively considered in the design stage in order to reduce the impact on marine ecological environment not only account for the safety of nuclear power plants, but also promote the coordinated development of nuclear power industry and marine ecological protection.(随着我国核电发展的加快，核电生态环境问题逐步受到关注。目前我国在运核电厂均采用海水直流冷却方式，取排水构筑物的建设对周边水动力及冲淤环境造成一定影响。通过比较我国部分核电厂取排水方式发现，暗涵排水方案对周边水动力及冲淤环境影响较小，在涨、落潮南北方向±200 m、东西方向±100 m范围内，平均流速变化仅为0.01 m·s-1；在距离排水口中心200 m的范围内，冲刷深度超过0.3 m。垂直岸取水方案对周边水动力及冲淤环境影响相对较大，平均流速变化0.05 m·s-1的最远距离可达约2.4 km，取水明渠两侧淤积厚度大多在0.2~1.0 m。除海工构筑物对水动力和冲淤环境有一定影响外，核电厂运行对周边海洋生态环境的影响主要为取水卷塞及卷载效应、温排水和余氯的排放。建议在核电厂设计阶段综合考虑优化取排水方案，在优先保障核电安全的基础上尽量降低对海洋生态环境的影响，推进核电产业与海洋生态保护协同发展。)